Current tobacco use is associated with higher rates of implant revision and deep infection after total hip or knee arthroplasty: a prospective cohort study. Issue 1 (December 2015) - Singh, Jasvinder; Schleck, Cathy; Harmsen, W.; Jacob, Adam; Warner, David; Lewallen, David
Abstract Background Tobacco smoking is a risk factor for several adverse post-operative outcomes. We aimed to compare the rates of complications in current tobacco users and non-users who underwent primary total hip arthroplasty (THA) or total knee arthroplasty (TKA). Methods All patients who underwent primary THA or TKA at the Mayo Clinic from 2010–2013 were included in the study. Current tobacco use was defined as the use of cigarettes, cigars, pipes, or smokeless tobacco reported at the time of index THA or TKA; current non-users were former users or never users. We used Cox proportional hazards regression to assess the association of current tobacco use status with each post-THA/TKA complication, using hazard ratios and 95 % confidence intervals (CI). Results Tobacco use status was available for 7926 patients (95 %) and not available for 446 patients (5 %); 565 (7 %) were current tobacco users. Compared to non-users, current tobacco users were more likely to be male (p < 0.001), and less likely to be obese (p ≤ 0.008), be older than 60 years, have Charlson score >0 or have undergone TKA rather than THA (p < 0.001 each). The hazard ratios for deep infection (2.37; 95 % CI 1.19, 4.72;p = 0.01) and implant revision (1.78; 95 % CI 1.01, 3.13;p = 0.04) were higher in current tobacco users than in non-users. No significant differences were noted for periprosthetic fractures or superficial infections. Conclusions We noted that current tobacco use was associated with high risk of deep infection and implant revision after primary THA or TKA. Future studies should determine the optimal time for tobacco use cessation before elective surgeries such as THA and TKA to improve short-term and long-term arthroplasty outcomes.